(untitled) (Fiep Bulletin - online, 2014)
The paper is inspired by the initiative of Physical Education teachers from the Municipality of Rio de Janeiro ( PCRJ ) - 8th CRE who observed, within its Coordination, the existence of high number of graduates, without that academic excellence, necessarily, reflect or spread in classes. Considering this fact, they decided to set up within school, but independently of the municipal administration, a Center of Studies, aiming at the collective discussion on the Physical Education situation in their area, seeking to contextualize theory, practice and administrative management . Thus, since 2007, with many debates, not always consensual, the issues of literacy and health promotion in elementary school have become recurrent themes and subject of many studies, which resulted in the possibility, and pointed to the relevance, of this article, which aims to reaffirm the importance of motricity in learning and in health promotion in this stage of schooling, from a bias that aggregates Neurosciences to the analysis of the theme and reaffirms motricity as cognition, base of health and full human development. The methodology was the literature review and their findings were quite consistent for the understanding about the close relationship between corporeity, motricity, emotions, cognition, learning and health. The recent contributions of Neurosciences brought the demands for a reassessment of many theories and practices in Physical Education, including the Cartesian and mechanistic body vision, passed in review by the, still under construction, corporeity conception, in developments whose scope is not even delimited, but undoubtedly, is subject of interest to Physical Education teachers and debate of which this article intends to participate.